Witnessing to Christ Today: Promoting Health and Wholeness for All (International review of mission, 2012)
The global health situation at the beginning of the third millennium is alarming. While countries in the global North spend huge amounts of money providing high-tech medicine for their citizens, many people in resource-limited settings still do not have access to basic health care. These people bear an unjust burden of disease, and tens of thousands die every day of diseases that can be treated and often cured. In this regard, the contribution of Christian churches to health care is sorely needed. Already, churches and faith-based organizations are important health providers in many countries. This is especially the case with regard to people in remote areas and in resource-limited settings, and with marginalized groups in these and other places. In addition to the engagement by Christian bodies in health care, in many churches, especially the fast-growing churches of the global South, spiritual healing is becoming increasingly important. These churches seek to provide healing through prayer, blessing, the laying on of hands, and anointing with oil. However, many inside and outside the churches are not so confident that the churches' engagement in the field of health and healing is essential to their mission. Some argue that the churches should only be involved in health care provision if there are no secular health providers available. Also, whilst others insist on the use of exclusively “spiritual” means to overcome illness, many question whether Christians today should still seek to overcome illness through this approach. Against this background, the World Council of Churches (WCC) and the German Institute for Medical Mission (DIFAEM) wish to contribute to an understanding of the healing mission of the church today. Both organizations are engaged in the field of mission and healing, and have a long history in dealing with questions about the Christian healing ministry. Since its inception, the WCC has regarded issues related to health as part of its core work. Health care and theological questions on health and healing have been on the agenda of WCC programmes on mission, as well as those dealing with justice and diakonia. For many years, the WCC's Christian Medical Commission guided the organization's work on health and healing. DIFAEM has been a partner with the WCC in worldwide discussions on the healing mission of the churches since the mid-1960s, and a leader in the promotion and implementation of the concept of primary health care. In 2005, the world mission conference in Athens, Greece, considered the theme, “Come Holy Spirit, Heal and Reconcile: Called in Christ to Be Reconciling and Healing Communities,” and strongly reaffirmed the healing mission of the church. In 2007, the WCC and DIFAEM jointly called for a “study group on mission and healing” to follow up the Athens mission conference. This study group was subsequently mandated to work on the Christian understanding of the healing mission of the church, and to promote Christian engagement in the field of health. The members of the group are theologians and medical professionals from four continents and various denominations. The objectives of the group include: to clarify the holistic and integrated nature of Christian mission and healing, based on biblical theology; to demonstrate ways in which Christian communities can contribute towards health and healing in contemporary contexts. In this article, the study group offers a summary of the ecumenical discussions on health, healing and wholeness that were documented in WCC publications issued between 1965 and 2005. The main insight of these discussions was that health is not only physical and/or mental well-being but includes the social and spiritual and other dimensions as well. This is reflected in the definition of health approved by the WCC in 1989: “Health is a dynamic state of well-being of the individual and society, of physical, mental, spiritual, economic, political, and social well-being – of being in harmony with each other, with the material environment and with God.” This expanded definition of health leads us to the Christian understanding that healing is not only and not primarily medical. Healing then includes, for instance, addressing the spiritual needs of sick persons as well as working for justice, peace and the integrity of creation. Moreover, the role of congregational and non-congregational communities and faith- based and governmental organizations as well as individual Christians in the field of health and healing becomes obvious. Faith communities/congregations in particular are called to practise healing in various ways. They contribute to healing as social networks, as places of teaching and learning together, and as advocates for justice, peace and the integrity of creation. Healing is practised in liturgical acts and through nurturing and practicing charismatic gifts, through counselling and caring, and through creating safe and open spaces. Faith communities have a role in promoting primary health care, and can become vital partners of the formal health sector. This contribution aims to reaffirm the healing mission of the church, and to encourage churches, plus Christian communities and organizations, to engage in this ministry, and thus take part in God's mission of transforming the world. Beate JAKOB